2012 Electricity Profiles - Nations Unies (United Nations, 2015)
The 2012 Electricity Profiles contains electricity profiles for about 200 countries and territories, providing detailed information on production, trade and consumption of electricity, net installed capacity and thermal power plant input and efficiency for most countries.